Designing brand identity : an essential guide for the whole branding team - Wheeler, Alina, 1948- (Wiley, 2013)
"A revised new edition of the bestselling toolkit for creating, building, and maintaining a strong brand. From research and analysis through brand strategy, design development through application design, and identity standards through launch and governance, Designing Brand Identity, Fourth Edition offers brand managers, marketers, and designers a proven, universal five-phase process for creating and implementing effective brand identity. Enriched by new case studies showcasing successful world-class brands, this Fourth Edition brings readers up to date with a detailed look at the latest trends in branding, including social networks, mobile devices, global markets, apps, video, and virtual brands. Features more than 30 all-new case studies showing best practices. Updated to include more than 35 percent new material. Offers a proven, universal five-phase process and methodology for creating and implementing effective brand identity"--Vydavatelská anotace
Keywords: řízení značky; obchodní značky; identita organizace; image organizace; grafický design; brand management; brand name products; corporate identity; corporate image; graphic design; příručky; případové studie; handbooks and manuals; case studies